Secure IoV communications for smart fleet systems empowered with ASCON - Bhuvaneshwari A J; P. Kaythry (Scientific Reports)
Abstract The Internet of Vehicles (IoV) is crucial in facilitating secure and efficient vehicle-infrastructure communication. Nevertheless, with an increasing reliance on the IoV in modern logistics and intelligent fleet systems, cyberattacks on vital supply chain information pose a far greater threat. This research presents the ASCON, a low-power cryptographic algorithm, with the Message Queued Telemetry Transport (MQTT) protocol for secure IoV communications. Integration of a deep learning model that is suited for real-time anomaly detection and breach prediction. The novelty of this study is the hybrid framework that uses lightweight cryptographic methods coupled with deep learning-based threat protection. Therefore, it is resilient against a wide range of cyber-attacks, including password cracking, authentication compromises, brute-force attacks, differential cryptanalysis, and Zig-Zag attacks. The system employs Raspberry Pi boards with authentic industrial vehicluar dataset and offers a remarkable encryption rate of 0.025 s, takes 0.003 s for hash generation, and detection of tampering takes 0.002 s. By bridging the gap between high-level cryptography and proactive and smart security analytics, this work not only fortifies fleet management systems but also makes substantial contributions to the overall objectives of enhancing safety, sustainability, and operational robustness in autonomous vehicle networks.